Effects of repetitive transcranial magnetic stimulation on cognitive function and cholinergic activity in the rat hippocampus after vascular dementia - Xiao-Qiao Zhang; Li Li; Jiang-Tao Huo; Min Cheng; Lin-Hong Li (Neural Regeneration Research, 2018)
Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive treatment that can enhance the recovery of neurological function after stroke. Whether it can similarly promote the recovery of cognitive function after vascular dementia remains unknown. In this study, a rat model for vascular dementia was established by the two-vessel occlusion method. Two days after injury, 30 pulses of rTMS were administered to each cerebral hemisphere at a frequency of 0.5 Hz and a magnetic field intensity of 1.33 T. The Morris water maze test was used to evaluate learning and memory function. The Karnovsky-Roots method was performed to determine the density of cholinergic neurons in the hippocampal CA1 region. Immunohistochemical staining was used to determine the number of brain-derived neurotrophic factor (BDNF)-immunoreactive cells in the hippocampal CA1 region. rTMS treatment for 30 days significantly improved learning and memory function, increased acetylcholinesterase and choline acetyltransferase activity, increased the density of cholinergic neurons, and increased the number of BDNF-immunoreactive cells. These results indicate that rTMS can ameliorate learning and memory deficiencies in rats with vascular dementia. The mechanism through which this occurs might be related to the promotion of BDNF expression and subsequent restoration of cholinergic system activity in hippocampal CA1 region.